International finance and financial crises : essays in honor of Robert P. Flood, Jr. - Isard, Peter; Flood, Robert P.; Razin, Assaf; Rose, Andrew K (Boston : Kluwer Academic ; Washington D.C. : International Monetary Fund, 1999)
Contains the proceedings of a conference held in honor of Robert P Flood. This book includes five papers on topics in international finance; two of these papers, as well as the panel discussion, focus on speculative attacks and financial crises.
"Proceedings of a conference held in honor of Robert P. Flood, Jr. ... at the International Monetary Fund in Washington, DC on the occasion of ... [his] fiftieth birthday in January 1999"--P. [ix].
"Partly reprinted from the International tax and public finance, volume 6, no. 4 (1999)."
Includes bibliographical references and index.
oif 11/07/2016
Loans
Keywords: Flood, Robert P; International finance; Financial crises